Mapping learning conditions at work : A study of contextual factors influencing the learning environment at Vaisala Oyj. - Sundström, Sissel (My University, 2018)
Companies today face a complex business environment, where the situation on markets can rapidly change. Organizational learning and development is a crucial competence for companies to be able to compete in the turbulent markets. In addition, development opportunities are becoming increasingly important for employees who are facing long careers and continuously changing requirements on the job market. To meet these demands, organizations need to invest in continuous, lifelong learning. However, building a learning organization in practice is not simple, as the context where learning takes place is often complex and ambiguous. The purpose of this study was to get an understanding of how learning can be facilitated in organizations. This was done by assessing the current state of the learning environment at Vaisala Oyj. by recognizing contextual factors that facilitated and inhibited learning in the organization. A qualitative case study method was selected as the empirical research approach in order to attain a thorough understanding of the learning environment of the organization. The thematic analysis of the interviews recognized that especially cognitive and cultural factors such as organizational values, employee motivation and open discussion culture were facilitating learning, whereas mainly procedural factors such as tools and procedures for planning, implementation and assessment of learning were inhibiting learning in the organization. The findings of this study are predominantly in line with the existing literature when it comes to the types of contextual factors that facilitate and inhibit organizational learning. The differences recognized mainly concern the cognitive and cultural facets of learning, which can be explained by the uniqueness of organizational culture across different companies, leading to distinct results. The findings of this study further suggest that contextual factors can simultaneously facilitate and inhibit learning in organizations. This finding indicates that dividing contextual factors to facilitating and inhibiting factors is not that simple, as the factors might have dimensions that are not apparent or transparent. Therefore, organizations should carefully examine their learning environment in order to be able to design appropriate mechanisms that support learning in their own, unique context.
Keywords: Organizational learning, learning organization, organizational learning mechanisms